Production of H5N1 Influenza Virus Matrix Protein 2 Ectodomain Protein Bodies in Tobacco Plants and in Insect Cells as a Candidate Universal Influenza Vaccine - Mbewana, Sandiswa; Mortimer, Elizabeth; Pêra, Francisco F. P. G.; Hitzeroth, Inga Isabel; Rybicki, Edward P. (Frontiers in Bioengineering and Biotechnology, 2015)
The spread of influenza A viruses is partially controlled and prevented by vaccination. The matrix protein 2 ectodomain (M2e) is the most conserved sequence in influenza A viruses, and is therefore a good potential target for a vaccine to protect against multiple virus subtypes. We explored the feasibility of a M2e-based universal influenza A vaccine candidate based on the highly pathogenic avian influenza A virus, H5N1. A synthetic M2e gene was human and plant codon optimised and fused in-frame with a sequence encoding the N-terminal proline-rich domain (Zera®) of the γ-zein protein of maize. Zera®M2e was expressed transiently in Nicotiana benthamiana and Sf21 baculovirus / insect cell expression systems, and Zera®M2e protein bodies (PBs) were successfully produced in both expression systems. The plant-produced Zera®M2e PBs were purified and injected into Balb/c mice. Western blot analysis using insect cell-produced Zera®M2e PBs and multiple tandem M2e sequences (5xM2e) fused with the avian influenza H5N1 transmembrane and cytosolic tail (5xM2e_tHA) confirmed the presence of M2e-specific antibodies in immunised mice sera. The immunogenicity of the Zera®M2e indicates that our plant-produced protein has potential as an inexpensive universal influenza A vaccine.